Pengaruh Strategi Promosi Terhadap Peningkatan Penjualan Kacamata Di Optik Duta Kampar Riau - Dolly Iman Suryanta; Rina Novalinda (CV. ITTC INDONESIA, 2023)
This scientific paper discusses the strategy and influence of promotion in increasing sales of glasses at Optics Duta Kampar Riau. The aim is to find out the promotion strategy and how much influence the promotion has on sales carried out by Optics Duta Kampar Riau. The type of research that the authors use is descriptive qualitative, where the methods used are observation and interviews. The author conducted interviews with respondents, the respondents I mean are Optics Duta Kampar Riau employees. After conducting interviews, the authors make observations or observations that aim to make the data that the authors get more complete and real. From the research results it is known that the promotion carried out by Optics Duta Kampar Riau is very important in increasing sales. The author suggests that Optics Duta Kampar Riau is always consistent in carrying out promotional activities so that promotions are carried out more effectively and can benefit Super Optics.